Students’ Acceptability and Attitude towards the Computer-Based Test (CBT) Mode for Testing Undergraduates in a Nigeria University - Uyigue, Amen Valentine; EGBERHA, Friday (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
Abstract Undergraduates’ acceptability and attitude towards CBT as the general mode of testing in undergraduate programs were considered in this study. The survey research design was adopted; the population consists of the students in the Faculty of Education at the University of Benin. A sample of 200 was drawn from the total number of students by random sampling. The instrument – Students Attitude and Acceptability of the CBT Scale- was used for data collection, it was developed by the researchers, and the instrument had a reliability coefficient of .076 and .082 for sections B and C respectively. Descriptive statistics (Mean and Standard Deviation) were used in answering the research questions while inferential statistics (t-test and ANOVA) were used for hypotheses testing. All statistical data analysis were done using the IBM-SPSS statistical package version 20. Findings revealed that the students have positive Attitude towards the CBT and the level of acceptability of the CBT was found to be high. However, there was no significant difference in the attitude and acceptability by sex, but there was a difference in acceptability by area of study whereas there was none in attitude. It was recommended among others that CBT be introduced as the general mode of testing in the undergraduate programmes except otherwise, in areas where it is not practicable.